Pengaruh Pengelolaan Keuangan dan Pemberdayaan Wanita Nelayan terhadap Kesejahteraan Rumah Tangga - Sulkiah, Sulkiah (Lembaga Yasin AlSys, 2021)
This study seeks to examine the effect of financial management and empowerment on household welfare. The sample of this research is 171 respondents who live on the coast of East Lombok. Data analysis used structural equation model. The research findings prove that the financial management and empowerment of women fishermen have a significant positive impact on household welfare. This means that women fishermen need to increase their financial knowledge as well as confidence and ability to control their financial condition.